Respuesta :

Answer:

Part 1) [tex]z=4\sqrt{2}\ units[/tex]

Part 2) [tex]x=18\ units[/tex]

Part 3) [tex]y=12\sqrt{2}\ units[/tex]

Step-by-step explanation:

step 1

Find the value of z

In the smaller right triangle IFG of the figure

Applying the Pythagoras Theorem

[tex]6^{2}=2^{2}+z^{2}[/tex]

[tex]z^{2}=6^{2}-2^{2}[/tex]

[tex]z^{2}=32[/tex]  

[tex]z=4\sqrt{2}\ units[/tex]

step 2

In the right triangle HFG

Applying the Pythagoras Theorem

[tex]x^{2}=y^{2}+6^{2}[/tex]

[tex]y^{2}=x^{2}-36[/tex] -----> equation A

step 3

In the right triangle HIG

Applying the Pythagoras Theorem

[tex]y^{2}=z^{2}+(x-2)^{2}[/tex]

[tex]y^{2}=32+(x-2)^{2}[/tex] -----> equation B

step 4

equate equation A and equation B

[tex]x^{2}-36=32+(x-2)^{2}\\x^{2}-36=32+x^{2}-4x+4\\4x=36+36\\4x=72\\x=18\ units[/tex]

step 5

Find the value of y

Substitute the value of x in the equation B

we have

[tex]x=18\ units[/tex]

[tex]y^{2}=32+(18-2)^{2}[/tex]

[tex]y^{2}=32+(16)^{2}[/tex]

[tex]y^{2}=288[/tex]

[tex]y=12\sqrt{2}\ units[/tex]